Peat dynamics in the Angolan Highlands - Lourenco, Mauro Cesar (University of the Witwatersrand, Johannesburg, 2023)
The Angolan Highlands is a war stricken, threatened, and under-studied area. The region is hydrologically and ecologically important and supports extensive tropical peatland deposits. Peatland preservation has been acknowledged to address climate change, is sensitive to drought and fire, and is directly influenced by vegetation and hydrological conditions. However, little research has been conducted in the Angolan Highlands. This study addresses gaps in the literature through four key contributions. The first is a critical review of peat definitions: the implications of disparate definitions are detailed, and a new proposed definition for peatlands in the interest of climate science is provided. The second is the first map of peatland extent in the Angolan Highlands, containing details on the age and growth dynamics. The study presents a conservative estimate of peatland extent that is much larger than previously estimated for Angola and is a crucial first step in facilitating the preservation of this deposit. The third contribution is the first historical assessment of drought and vegetation response in the region. This contains a 40-year drought and 20-year vegetation history, demonstrating that drought occurrence is increasing and there is a strong relationship between precipitation and the peatland vegetation region. The fourth contribution is the first assessment of the contemporary (2001-2020) fire regime of these peatlands, and reveals that among all land cover classes, peatlands burn more frequently and at a higher proportion. Investigation into the peat dynamics of the Angolan Highlands indicate that they have critical importance and are naturally resistant to both droughts and fire. Failure to preserve these deposits will have direct implications on the communities, environment, and surrounding areas.
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Angolan Highlands; Carbon; Drought; Fire; Peat; Remote Sensing; UCTD; SDG-13: Climate action